2019
DOI: 10.1038/s41746-019-0078-0
|View full text |Cite
|
Sign up to set email alerts
|

Digital biomarkers of mood disorders and symptom change

Abstract: Current approaches to psychiatric assessment are resource-intensive, requiring time-consuming evaluation by a trained clinician. Development of digital biomarkers holds promise for enabling scalable, time-sensitive, and cost-effective assessment of both psychiatric diagnosis and symptom change. The present study aimed to identify robust digital biomarkers of diagnostic status and changes in symptom severity over ~2 weeks, through re-analysis of public-use actigraphy data collected in patients with major depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 8 publications
2
99
1
Order By: Relevance
“…This level of accuracy in diagnostic classification is greater than published inter-reliability rates for second raters using the Structured Clinical Interview for the DSM (SCID). And results showed that actigraphy data predicted the majority of variation in patients’ depression severity over an ~2-week period [ 66 ].…”
Section: The State Of the Science Of Digital Health Data-driven Appromentioning
confidence: 99%
“…This level of accuracy in diagnostic classification is greater than published inter-reliability rates for second raters using the Structured Clinical Interview for the DSM (SCID). And results showed that actigraphy data predicted the majority of variation in patients’ depression severity over an ~2-week period [ 66 ].…”
Section: The State Of the Science Of Digital Health Data-driven Appromentioning
confidence: 99%
“…Also these digital biomarkers are more in line with the phenomenological understanding of behavioural therapies. The quantification of behavioural and consciousness involving processes can assist squaring the circle of qualia-related outcome [6,7].…”
Section: Doi: 101159/000506672mentioning
confidence: 99%
“…Digital phenotyping is an especially attractive clinical tool for substance use treatment during the COVID-19 pandemic, as it not only operates remotely but is also convenient for patients (no active input required), is not administratively burdensome, and may be an effective way to address historic challenges in detecting problematic substance use behaviors and delivering timely clinical interventions. Digital phenotyping has shown initial success in relapse prediction for schizophrenia [ 12 ], bipolar disorder [ 13 , 14 ], and mood disorder detection [ 14 ]. We describe three broad applications of digital phenotyping for addiction treatment, highlighting their potential clinical use, state of evidence, and next steps for implementation.…”
Section: Introductionmentioning
confidence: 99%